Effect of Season on Oocyte Recovery, Quality and Morphometry in Goat - SANGHA, G K; BHATIA, H; KHERA, K S (The Indian Journal of Animal Reproduction, 2023)
Seasonal effects have the potential to influence the follicular dynamics. The prerequisite for thecontemporary embryo transfer technology is the availability of good quality oocytes. The present studywas undertaken to observe effects of season on oocyte retrieval, quality and morphometry in goat.Maximum numbers of small (3mm) follicles were obtained during rainyseason. The percentage recovery of oocytes was highest during rainy season though the proportion ofgood quality oocytes was more during winter. The size of the oocyte showed a direct relation with thefollicular size. The diameter of small as well as large oocytes was reduced during summer. The presentstudy reports a seasonal relationship of ovarian morphology as implicated by the quality of oocytes inslaughtered goats.
Keywords: Goat; oocyte; Recovery; Quality; Morphometry; Season and Heat stress